Обобщенное преобразование Харди и операторы Теплица в пространствах типа ВМОА - Шамоян, Р.Ф. (Український математичний журнал, 2001)
Вивчено дію узагальненого зображення Харді у класах ВМОА в полікрузі та наведено критерій обмеженості операторів Тепліца, що діють у просторі типу ВМОА в одиничному крузі. We study the action of the generalized Hardy transformation in the BMOA classes in a half-disk and present a criterion for the boundedness of the Toeplitz operators acting in a BMOA-type space in the unit disk.